Risk management practices of transportation companies: practitioners’ perspective - Mustapha, Mazlina; Mustapah, Nurul Janna (Inderscience Publisherseditor@inderscience.com, 2020)
It is claimed that organisations face challenges and risks in their operations which hinder their ability to achieve the organisational objectives. Prior studies suggest the implementation of risk management to assist the organisations in ensuring their sustainability in the long run. Risk management practices focus on creating responses to the inherent uncertainties of managing complex situations faced by the organisations, especially in service sector. Delivering quality services is very important in service sector in order to maintain their market share. Thus, this study aims to examine the implementation of risk management in the transportation industry, one of the important service sectors in Malaysia. Fifteen head of operations and managers of transportation companies were interviewed. Findings suggest that the implementation of risk management assist the companies in monitoring the drivers, controlling the maintenance costs of the buses and planning for routes during slack periods. This study provides information to transportation companies about the importance of risk management practices in their operations.